The Semiotics of Snapchat Filters: Understanding Their Influence on User Self-Presentation - Alamyar, Iqbal Hussain; Hussain, Javid (INJECT (Interdisciplinary Journal of Communication), 2024)
This research explores the semiotics of Snapchat filters and their influence on user self-presentation. Utilizing the Media Culturalist Perspective and Saussurean Visual Semiotic Theory, it investigates how Snapchat filters, as visual signs, construct meaning and shape user self-presentation on the platform. The study employs a qualitative research design, collecting data through semi-structured interviews with Snapchat users and performing a visual semiotic analysis of the filters. Thematic analysis identifies patterns within the data, providing insights into the cultural implications of Snapchat filters. This research fills a significant gap in existing literature by focusing on the cultural impact of these filters, integral to the Snapchat experience. The findings highlight the role of visual elements in social media self-presentation, contributing to broader discussions on digital culture. These qualitative insights reveal how Snapchat filters shape online self-presentation, offering implications for users, the platform, and future research.